Modeling priming effects on microbial consumption of dissolved organic carbon in rivers. Issue 5 (29th May 2014) - Hotchkiss, E. R.; Hall, R. O.; Baker, M. A.; Rosi‐Marshall, E. J.; Tank, J. L.
Abstract Rivers receive and process large quantities of terrestrial dissolved organic carbon (DOC). Biologically available (unstable) DOC leached from primary producers may stimulate (i.e., prime) the consumption of more stable terrestrially derived DOC by heterotrophic microbes. We measured microbial DOC consumption (i.e., decay rates) from contrasting C sources in 10 rivers in the western and Midwestern United States using short‐term bioassays of river water, soil and algal leachates, glucose, and commercial humate. We added inorganic nutrients (ammonium and phosphorus) to a subset of bioassays. We also amended a subset of river, soil, and commercial humate bioassays with glucose or algal leachates to test the hypothesis that unstable DOC primes consumption of more stable DOC. We used prior measurements of source‐specific DOC bioavailability, linked with a Bayesian process model, to estimate means and posterior probability distributions for source‐specific DOC decay rates in multisource bioassays. Modeled priming effects ranged from a −130 to +370% change in more stable DOC decay when incubated with unstable DOC. Glucose increased modeled river DOC decay by an average of 87% among all rivers. Glucose and algal leachates increased soil leachate and commercial humate decay by an average of 25% above background rates. Inorganic nutrient additions did not have consistent effects on DOC decay, likely because most of the study rivers had high ambient background nutrients. Our results demonstrate that the priming effect can augment DOC decay in rivers. In addition, Bayesian models can be used to estimate mechanisms driving aquatic ecosystem processes that are difficult to measure directly.